Sosialisasi Pencegahan Penyebaran Covid-19 Kepada Pedagang di Pasar Baru Kefamenanu - Lukas Pardosi; Desta Gloria Siahaan (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2022)
This community service was held because of the low awareness of sellers in Pasar Baru to wear masks and the lack of knowledge of sellers about how to wear masks correctly. The socialization activity for the prevention of the spread of Covid-19 to sellers at Pasar Baru Kefamenanu was held for one day. Pasar Baru is located on Jl. Sisingamangaraja, Benpasi, Kefamenanu City, North Central Timor, East Nusa Tenggara, Indonesia. The main target of this activity is the sellers operating in the new market area of ​​Kefamenanu city. The activity began with socializing the prevention of the spread of Covid-19 and closed with the distribution of masks for free to sellers at Pasar Baru Kefamenanu and how to use masks correctly.